2014
DOI: 10.1167/iovs.13-13631
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146 Inhibits Thrombin-Induced NF-κB Activation and Subsequent Inflammatory Responses in Human Retinal Endothelial Cells

Abstract: We uncovered a novel negative feedback regulatory mechanism on thrombin-induced GPCR-mediated NF-κB activation by miR-146. In combination with the negative feedback regulation of miR-146 on the IL-1R/toll-like receptor (TLR)-mediated NF-κB activation in RECs that we reported previously, our results underscore a pivotal, negative regulatory role of miR-146 on multiple NF-κB activation pathways and related inflammatory processes in DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 49 publications
2
66
0
Order By: Relevance
“…36,37,54,55 Quantitative (q)RT-PCR of miRNAs was performed using TaqMan microRNA assays (Applied Biosystems, Foster City, CA, USA), with small nuclear (sn)RNA U6 as a normalization control. Quantitative RT-PCR of mRNAs was performed using QuantiTect primer assays and QuantiFast SYBR Green RT-PCR kit (Qiagen, Germantown, MD, USA), with 18s rRNA as a normalization control as described previously.…”
Section: Rna Preparation and Quantitative Rt-pcrmentioning
confidence: 99%
See 3 more Smart Citations
“…36,37,54,55 Quantitative (q)RT-PCR of miRNAs was performed using TaqMan microRNA assays (Applied Biosystems, Foster City, CA, USA), with small nuclear (sn)RNA U6 as a normalization control. Quantitative RT-PCR of mRNAs was performed using QuantiTect primer assays and QuantiFast SYBR Green RT-PCR kit (Qiagen, Germantown, MD, USA), with 18s rRNA as a normalization control as described previously.…”
Section: Rna Preparation and Quantitative Rt-pcrmentioning
confidence: 99%
“…Previously, we reported one of the first miRNA transcriptomes of the retina and retinal endothelial cells (RECs) of diabetic rats, and identified a series of miRNAs involved in early DR. 36 Among DR-related miRNAs, we demonstrated that miR-146 is a pivotal negative feedback regulator of nuclear factor kappa-B (NF-jB) activation. 36,37 Nuclear factor kappa-B is a master regulator of inflammatory responses, and plays critical roles in inflammatory damages to RECs and retinal microvasculature during development of DR. [38][39][40][41][42][43][44] Nuclear factor kappa-B induces expression of proinflammatory molecules, including intercellular adhesion molecule 1 (ICAM1), 45 a key endothelial adhesion molecule to recruit leukocytes onto endothelial cell surface, and facilitate leukostasis and propagation of inflammatory responses, contributing to REC cell death and DR development. [46][47][48][49] We showed that miR-146 inhibited IL-1R/ Toll-like receptor (TLR)-mediated NF-jB activation pathway by targeting key adaptor molecules, interleukin-1 receptor-associated kinase 1 (IRAK1) and TNF receptor-associated factor 6 (TRAF6), 36,50 and prevented IL-1b-induced damage to retinal endothelial barrier function in vitro.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of miRs have been shown to be significantly regulated in the retinas or retinal ECs (RECs) in streptozotocin-induced or Akita (type I diabetic) DR animal models or in the oxygen-induced retinopathy model (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Particularly, miR-146a and miR-146b are upregulated in the RECs of diabetic rats and act as negative feedback on NF-B activation to control the inflammatory response (23,33); miR-200b and miR-126 are downregulated in a DR mouse model and regulate VEGF expression during retinal neovascularization (25,29); miR-200b downregulation was also found in the retinas of patients with diabetes (25,34). However, miR-200b was also shown to be significantly upregulated in the retinas of Akita rats and could contribute to increased cell death in DR (26).…”
mentioning
confidence: 99%